IDENTIFIKASI KERAPATAN TUTUPAN MANGROVE PULAU GUSUNG MENGGUNAKAN CITRA LANDSAT 8 - Ghina Yusriyyah Salma; Adhil Nur Muhammad; Raihan Cahara Winaya Adiwiria; Riki Ridwana; Lili Somantri (Jurnal Sains Informasi Geografi (J SIG), 2022)
Mangrove forest is one of the ecosystems that live in coastal areas and has a muddy substrate. Mangroves have an important role in maintaining water productivity and supporting the life of Indonesia's coastal areas. However, the increasing desire to convert or exploit mangrove forests can trigger a periodic decline in the number of mangrove forests, which will result in changes in the environment of coastal ecosystems, and have an impact on physical, biological and economic decline. This research objective is to analyze changes in mangrove forests using remote sensing data. The study used data for 2015 and 2019, which are located in the coastal mangrove forest of Gusung Island Bontoharu Subdistrict, Selayar Islands Regency, South Sulawesi Province. Normalized Difference Vegetation Index (NDVI) formula is used to calculate and classify in obtaining land cover. The results showed that the mangrove forest in the coastal area of Gusung Island experienced an increase in vegetation density. This can be an example for other areas so that mangrove forests need to be preserved and protected from damage.